Genotypic characterization of Giardia lamblia, Entamoeba species and Cryptosporidium species among children in Kiambu County, Kenya - Liza Kiende Mwirigi; Cecilia Mbae; Margaret Muturi; Scholastica Mathenge; Michael Mugo; Tabitha Irungu; Benjamin Ngugi; Erastus Mulinge (Food and Waterborne Parasitology)
Enteric parasitic infections are a leading cause of diarrheal disease and malnutrition in low- and middle-income countries like Kenya. Among the most prevalent protozoan pathogens in children are Entamoeba histolytica, Giardia lamblia, and Cryptosporidium species. However, data on their genetic diversity, co-occurrence, and variability in Kenya remain limited. This study investigated the genetic diversity of G. lamblia, Entamoeba spp., and Cryptosporidium spp. in children aged 10 years and below in Kiambu County, Kenya. A total of 550 stool samples were analyzed for enteric parasites using formal-ether concentration and Modified Ziehl-Neelsen staining. Genomic DNA was extracted from microscopy-positive samples, and species-specific nested polymerase chain reaction was performed to genotype Entamoeba spp. using the 18S ribosomal RNA gene. For G. lamblia and Cryptosporidium spp., nested PCR and sequencing targeted the βeta-giardin, triose phosphate isomerase, and 60-kDa glycoprotein genes, respectively. Microscopy detected Entamoeba spp. (29.6 %, 163/550), G. lamblia (14.6 %, 80/550), and Cryptosporidium spp. (1.3 %, 7/550). PCR analysis identified E. histolytica (3.3 %, 18/550), E. dispar (3.8 %, 21/550), E. moshkovskii (1.6 %, 9/550), E. coli (13.1 %, 72/550), and E. hartmanni (1.5 %, 8/550). Sequence analysis of the tpi and β-giardin genes identified G. lamblia assemblages A (20/50) and B (30/50). All assemblage A isolates were classified as sub-assemblage AII (20/20), while assemblage B isolates were further subdivided into sub-assemblages BIII (21/30) and BIV (9/30). All Cryptosporidium isolates were identified as C. hominis, with subtypes IbA9G3 (5/6) and IeA11G3T3 (1/6). Microscopy results revealed a significant association between Entamoeba spp. and Cryptosporidium spp. with both age groups and study sites. Entamoeba dispar by PCR and G. lamblia by microscopy showed significant differences between study sites. Additionally, the distribution of G. lamblia assemblages A and B, along with sub-assemblages AII, BIII, and BIV, differed significantly between the study sites. Among these, only sub-assemblage BIV showed a significant association with age groups. The detection of E. histolytica alongside related Entamoeba spp. underscores the importance of molecular diagnostics for accurate amoebiasis management and epidemiological surveillance. Additionally, the identification of G. lamblia sub-assemblages AII, BIII, and BIV, as well as C. hominis subtypes, suggests anthroponotic transmission, emphasizing the need for improved sanitation and public health interventions.